SAKSI KELUARGA DALAM PERKARA PERCERAIAN PADA PENGADILAN AGAMA MAROS - Nur, Dwi Utami Hudaya (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
Everyone is considered capable of being a witness, unless the law dictates otherwise. The prohibition of family witnesses to be presented in divorce trials is a prohibition that is devoted to divorce cases for the sake of avoiding the witness's non-objective attitude in giving testimony. The main research problem was How is the effectiveness of the family witnesses prohibition implemented in divorce cases according to Article 172 clause (1) RBg? This study employed empirical normative legal research methods. The results showed that the implementation of the family witnesses prohibition in divorce cases at the Maros Religious Court was ineffective due to the existence of family witnesses who were still presented by the plaintiff or defendant in court on the grounds of divorce outside syiqaq by considering family closeness to husband and wife which made family witnesses know the household condition.